The Costs of Bureaucracy and Corruption at Customs: Evidence from the Computerization of Imports in Colombia (2019)
Customs face a difficult tradeoff between, on one side, collecting tariff revenues and preventing smuggling, and on the other side, avoiding creating additional barriers to trade. They also tend to concentrate discretionary power in the hands of officials whose decisions can bear high costs for the firms, creating room for rent extraction. In this context, information technologies can limit direct interactions, reduce transaction costs and allow local businesses to better take of the benefits of international trade. We assess the effects of the computerization of import transactions on plants¿ growth in Colombia. The reform occurred sequentially in the different customs between 2000 and 2005, allowing us to use a triple-difference strategy, comparing the change in outcome variables of plants that were importing before the beginning of the reform, to the one of firms that were not importing (less likely to be affected by changes at customs). We find that the computerization of imports led to an increase of 6 log points in the firms¿ value added along with consequent increases in employment, productivity and tax collection. However, it generated winners (importing firms) and losers (non-importing firms). Our investigation of the channels reveals a reduction in corruption judiciary cases at treated customs, as well as a reduction of time to clear customs and its unpredictability. Our results support growing evidence of the high potential of proper use of information technologies to improve efficiency and tackle corruption in public administration with important consequences for the economy.